Pengaruh Pemasangan Fine Bubble Diffuser terhadap Nilai COD dan BOD Limbah Cair Palm Oil Mill Effluent - Akli, Khairul; Yolanda , Yolanda; Akbar, Addin; Senjawati, Maria Isfus (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
The rapid development of the palm oil industry, which cannot be denied, has an impact on the amount of industrial waste, particularly wastewater, requiring proper and effective treatment to reduce the impact of the damage. Wastewater treatment of Palm Oil Mill Effluent (POME) in an aerobic pond requires an adequate supply of oxygen so that its quality improves and becomes disposable, so it requires assistance from aeration media. A fine bubble diffuser was used as the aeration medium in this study. The aeration medium in this study was a fine bubble diffuser. The purpose of this research is to investigate the impact of installing a diffuser on the quality of the final wastewater, particularly the COD and BOD values, in the palm oil industry wastewater treatment. The analysis results for the wastewater parameters after the installation of the fine bubble diffuser revealed a significant reduction in the waste's COD and BOD values to 130 – 175 mg/L and 67 – 78 mg/L, respectively, making it more suitable for disposal to the environment.